The influence of health education using game-based learning methods on improving smoking prevention behavior among school-age children - Vina Dwi Lestari; Titih Huriah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Cigarettes are still the most common cause of death worldwide. Today, the younger generation's smoking behaviour is expanding to children's ages. Therefore, attractive smoking prevention to children with media is necessary. The aim of this research is to design game-based learning health education media and analyze the effect of health education on improving smoking prevention behaviour for school-age children. This study consists of 2 stages, designing Game-Based Learning with the Multimedia Development Life Cycle (MDLC) method and quasi-experimental research with control and intervention groups. Determination of the research location used proportionate stratified random sampling and simple random sampling. The study took place at three elementary schools (SDN) in Yogyakarta with a sample of children 10-12 years old for a month. Testing games took 54 children, and the sample size was 88 children; 44 children for the control group and 44 children for the intervention group. The analysis used the Wilcoxon, Mann-Whitney, and Cohen's Effect Size with the help of SPSS. Most respondents in testing game applications stated that the game function followed the objectives, increasing knowledge about smoking and its prevention. Respondents rated the game as easy to use, learn, and have a pleasant feeling when playing the game. All respondents also expressed their interest in distributing the game to their other friends. After one month of intervention, children's knowledge increased with a p-value of 0.001, attitudes with a p-value of 0.022, and behaviour with a p-value of 0.019. Health education using the Game-Based Learning method could improve school-age children's knowledge, attitudes, and behaviour. Abstrak: Rokok masih merupakan penyebab paling sering terjadinya kematian di seluruh dunia. Perilaku merokok saat ini banyak dilakukan oleh generasi muda dan meluas ke usia anak-anak. Pencegahan inisiasi merokok pada anak penting untuk diimplementasikan dengan menggunakan media yang menarik untuk anak-anak. Tujuan penelitian ini adalah merancang media edukasi kesehatan dengan game based learning dan menganalisis pengaruh edukasi kesehatan terhadap peningkatan perilaku pencegahan merokok anak usia sekolah. Penelitian ini terdiri dari 2 tahapan yaitu perancangan media edukasi dengan metode Multimedia Development Life Cycle (MDLC) dan penelitian quasi eksperimental dengan kelompok kontrol dan intervensi. Penentuan tempat penelitian menggunakan proportionate stratified random sampling dan pengambilan sampel dengen simple random sampling. Penelitian dilakukan di 3 SDN di Kota Yogyakarta dengan sampel anak usia 10-12 tahun. Pengujian media menggunakan responden sebanyak 54 anak, kelompok kontrol sebanyak 44 anak dan kelompok intervensi 44 anak. Intervensi game based learning dilakukan selama 1 bulan. Analisis menggunakan Uji Wilcoxon, Mann-Whitney test dan Cohen's Effect Size dengan bantuan SPSS. Responden dalam pengujian media menyatakan bahwa setuju game dapat meningkatkan pengetahuan tentang pencegahan merokok dan menilai game mudah untuk digunakan, dipelajari, serta menimbulkan perasaan menyenangkan saat memainkan game. Seluruh responden berminat untuk menyebarluaskan game kepada temannya. Setelah intervensi selama 1 bulan terjadi peningkatan pengetahuan anak dengan p-value 0,000, sikap dengan p-value 0,022 dan perilaku dengan p-value 0,019. Pendidikan kesehatan dengan menggunakan media game dapat meningkatkan pengetahuan, sikap dan perilaku anak usia sekolah.